Efektivitas Penerapan Model Pembelajaran Kooperatif Tipe Team Games Tournament Dengan Media Number Card Terhadap Penguasaan Mufradat - Novita, Novita; Taubah, Miftachul; Syaifullah, Syaifullah (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
The purpose of this study was to determine how effective the cooperative learning model using Team Games Tournament with the help of Number Cards on students' mastery of mufradat in class X A Madrasah Aliyah. With the subject matter of "yaumiyyah", this research was conducted at Madrasah Aliyah Class X A. This research is a type of quantitative experiment with a pre-test and post-test design. The purpose of the pre-test and post-test design is to determine whether or not the treatment has an influence of the independent variable on the dependent variable. In addition, the sample of this study was collected from class X A of Madrasah Aliyah, which consisted of 15 students. This sample was obtained through saturated sampling technique. In this study, all students of class X A Madrasah Aliyah were selected as the population because they were easily accessible to the researcher. The data analysis techniques used in this study were Normality Test and T Test. In this study, there was an effect of the application of the Team Games Tournament learning model assisted by Number Card media on students' mastery of mufradat. From the results of the Normality Test calculation shows a sig value of 0.200> 0.05. And from the results of the T test calculation shows a sig value of 0.001 <0.05, which if it is concluded that there is an effect of using the Team Games Tournament type cooperative learning model assisted by Number Card media on students' mastery of mufradat